A ANALYSIS OF THE NEED FOR PUBLIC GREEN OPEN SPACE IN THE DOWNTOWN AREA OF BANGGAI LAUT REGENCY: - - Hendra Jultrisno Rusman (Fakultas Teknik Universitas Tompotika Luwuk, 2023)
The Community and Regional Government are making improvements in the infrastructure sector in tandem with the growth in activity and population in the City Center Area of the Banggai Laut Regency. As a result, the forest area decreases, which affects the amount of clean air available near the city center. Therefore, 20% of the total area of metropolitan areas must be set aside for the building of green open spaces. Currently, there are four parks built by the regional government of Banggai Laut Regency, all of which are in Tinakin Laut Village. They are Cardinalfish Park, Santai Park, Pujasera Park, and City Park, all of which are in Lompio Village, and all of which can be used by the community, with the exception of Pujasera Park, which is currently in the planning stage. According to the study's findings, 6,914 km2 of green open space is required for development in the City Center Area, however only 10.163 km2, or 29.398% of the total area of the 34.57 km2 City Center region, has been developed. However, due to the pattern of population dispersion and activity, the distribution of green open space development surrounding the City Center Area is unequal.